Electromagnetics - Rothwell, Edward J.; Cloud, Michael J. (CRC Press, Taylor & Francis Group, 2018)
Providing an ideal transition from introductory to advanced concepts, this book builds a foundation that allows electrical engineers to confidently proceed with the development of advanced EM studies, research, and applications. Several application-oriented sections covering guided waves and transmission lines, particle dynamics, shielding, electromagnetic material characterization, and antennas have also been added.